Answer:
Option A: 3x + 5x - 4 = 1
Step-by-step explanation:
Given that:
3x + y = 1 ------------- eq1
y + 4 = 5x ------------ eq2
Now for substitution in eq1 we will get a value of y from eq2:
y = 5x - 4
Substituting in eq1 we get:
3x + 5x - 4 = 1
i hope it will help you!
The answer is A. Because you can’t lose the amount of steps you took.
Step-by-step explanation:
2 × (First Angle + Second Angle) = 360°
5x + 9x + 26 = 360°/2
14x + 26 = 180°
14x = 180 - 26
14x = 154
x = 154/14
x = 11°
The answer is B.